Complement C5a induces the formation of neutrophil extracellular traps by myeloid-derived suppressor cells to promote metastasis. (31st March 2022) - Ortiz-Espinosa, Sergio; Morales, Xabier; Senent, Yaiza; Alignani, Diego; Tavira, Beatriz; Macaya, Irati; Ruiz, Borja; Moreno, Haritz; Remírez, Ana; Sainz, Cristina; Rodriguez-Pena, Alejandro; Oyarbide, Alvaro; et al.
Abstract: Myeloid-derived suppressor cells (MDSCs) play a major role in cancer progression. In this study, we investigated the mechanisms by which complement C5a increases the capacity of polymorphonuclear MDSCs (PMN-MDSCs) to promote tumor growth and metastatic spread. Stimulation of PMN-MDSCs with C5a favored the invasion of cancer cells via a process dependent on the formation of neutrophil extracellular traps (NETs). NETosis was dependent on the production of high mobility group box 1 (HMGB1) by cancer cells. Moreover, C5a induced the surface expression of the HMGB1 receptors TLR4 and RAGE in PMN-MDSCs. In a mouse lung metastasis model, inhibition of C5a, C5a receptor-1 (C5aR1) or NETosis reduced the number of circulating-tumor cells (CTCs) and the metastatic burden. In support of the translational relevance of these findings, C5a was able to stimulate migration and NETosis in PMN-MDSCs obtained from lung cancer patients. Furthermore, myeloperoxidase (MPO)-DNA complexes, as markers of NETosis, were elevated in lung cancer patients and significantly correlated with C5a levels. In conclusion, C5a induces the formation of NETs from PMN-MDSCs in the presence of cancer cells, which may facilitate cancer cell dissemination and metastasis. Highlights: C5a promotes an integrin-independent amoeboid mode of migration in PMN-MDSCs. C5a triggers PMN-MDSC NETosis to favor tumor cell invasion and metastasis. C5a-mediated PMN-MDSC NETosis depends on the production of HMGB1 by cancer cells. C5a/C5aR1 blockade reduces the number of CTCs and the metastatic burden. NETosis markers are elevated in lung cancer patients and correlate with C5a levels.